Evaluation of fracture resistance of restored and endodontically treated teeth with different intraradicular retainers - Braga, Marcia Rachel Costa Lima; Sena, Neylla; Paulo Junior, Marcos; Oliveira, Tarcisio Tavares; Macedo Neto, Jose Costa de; Calderon, Paulo; Oliveira, Jonas Alves de (Research, Society and Development, 2023)
The objective of this study was to evaluate the fracture resistance of fragile premolars after restoration with different intraradicular retainers. For the fracture resistance test, 30 upper premolars were divided into three experimental groups (n=10), with G1 consisting of healthy teeth (control group); group G2 - teeth with fiberglass post (Reforpost, Angelus) and direct restoration with Filtek Z250 microhybrid resin (3M ESPE) and G3 - Teeth with polyethylene fiber (Ribbond Inc.) and direct restoration with Filtek microhybrid composite resin Z250 (3M ESPE). The samples were submitted to the fracture resistance test and the failures were evaluated. The results were analyzed using the Anova and T Test for fracture resistance, and the Kruskal-Wallis Test for the location and type of fracture, with p<0.05 always being used as the confidence level. The G1 group had the highest values, with 503.12N (+/- 262.20), with a statistical difference from the G2 and G3 groups, which had similar values ​​(p<0.05) for fracture resistance and for fracture location the most common among the three groups was the neck. It can be concluded that the restorations using fiber post and polyethylene fiber used as intraradicular retainers provided similar results in fracture resistance tests, demonstrating that the polyethylene fiber used as retainer can be considered as an option for the rehabilitation of endodontically treated teeth.